Diamond-copper composite heat dissipation substrate and preparation method thereof

CN122918463APending Publication Date: 2026-10-16SUZHOU HECHUAN CHEM TECH SERVICE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611182407.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]有鉴于此,本发明提供了一种金刚石-铜复合散热基板及其制备方法,其目的是解决现有技术中金刚石-铜复合材料界面热阻高、热膨胀系数难以兼顾匹配、梯度结构层间结合薄弱的技术问题

Benefits of technology

1.本发明在金刚石颗粒表面原位生长碳化钛纳米线阵列,而非简单形成致密碳化物薄膜。碳化钛纳米线自金刚石表面向外延伸并被铜基体所包覆,极大地增加了金刚石与铜之间的界面接触面积,形成了从金刚石到碳化钛过渡层再到碳化钛纳米线、最终嵌入铜基体的多级梯度界面结构。这种结构在金刚石颗粒与铜基体之间构建了高效的声子传输通道,显著降低了界面热阻,使复合材料的整体热导率得到大幅提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a diamond-copper composite heat dissipation substrate and a preparation method thereof, and belongs to the technical field of electronic packaging heat dissipation materials. The preparation method comprises the following steps: depositing a titanium layer on the surface of diamond particles; loading the titanium-plated diamond particles with a catalyst metal salt, and then performing reduction treatment in a hydrogen atmosphere, so that the catalyst metal salt is converted into metal catalyst particles; subsequently, the atmosphere is switched to a carbon-containing gas atmosphere to perform heat treatment, so that the titanium layer grows outward with the catalyst particles as the center, and is in-situ converted into a titanium carbide nanowire array; the surface-modified diamond particles and copper powder are mixed, and are layered and filled to form a powder blank with a gradient distribution of the volume fraction of the diamond; and after sintering, annealing in a reducing atmosphere is performed, and the diamond-copper composite heat dissipation substrate is obtained. The in-situ growth of the titanium carbide nanowire array significantly reduces the interface thermal resistance, and the gradient distribution of the diamond realizes the regulation of the coefficient of thermal expansion, so that the problems of high interface thermal resistance and difficult thermal expansion matching in the prior art are solved; and the prepared heat dissipation substrate has excellent heat conduction performance and good thermal cycle reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic packaging heat dissipation materials technology, and in particular to a diamond-copper composite heat dissipation substrate and its preparation method. Background Technology

[0002] With the rapid development of 5G communication, artificial intelligence, high-power semiconductor devices and phased array radar, the integration and power density of electronic components continue to rise, and the heat generation per unit area increases dramatically, which puts forward more stringent requirements on the thermal conductivity and thermal expansion matching performance of heat dissipation substrate materials.

[0003] Diamond possesses extremely high theoretical thermal conductivity (reaching over 2000 W / (m·K)) and a low coefficient of thermal expansion, while copper exhibits excellent thermal conductivity and good processability. Diamond-copper composite materials, prepared by combining these two materials, are considered ideal next-generation heat dissipation substrate materials for electronic packaging. However, existing diamond-copper composite materials still face the following prominent technical challenges in practical applications: First, there is the issue of interfacial thermal resistance. The poor wettability between diamond and copper makes it difficult to form a strong chemical-metallurgical bond, resulting in high interfacial thermal resistance and severely limiting the overall thermal conductivity of the composite material. To address this, the industry commonly uses carbide-forming elements (such as titanium, tungsten, and chromium) to coat the diamond surface to improve interfacial bonding. However, the resulting carbide transition layer is usually a dense thin film structure with relatively low intrinsic thermal conductivity, and the contact area with the copper substrate is limited, leaving considerable room for improvement in interfacial heat transfer efficiency.

[0004] Second, there's the issue of matching thermal expansion coefficients. The thermal expansion coefficients of semiconductor chips (such as GaAs, GaN, and SiC) are typically between 3 and 7 × 10⁻⁶. -6 Within the range of / K, the coefficient of thermal expansion of copper is approximately 17×10. -6 / K. Although the overall coefficient of thermal expansion of traditional uniformly distributed diamond-copper composite materials can be controlled by adjusting the volume fraction of diamond, the design of a single volume fraction makes it difficult to simultaneously meet the requirements of low thermal expansion matching with the chip contact surface and reliable connection with other packaging components (such as the shell and solder layer).

[0005] Third, the preparation of gradient structure composite materials faces challenges. To achieve gradient control of the coefficient of thermal expansion, some researchers have attempted to prepare gradient composite materials with a gradual change in diamond volume fraction along the thickness direction. However, simple gradient distribution only alleviates the thermal stress problem at the macroscopic level and does not fundamentally improve the thermal conductivity bottleneck at the microscopic interface between diamond particles and the copper matrix. The gradient interlayer interface remains a weak link in thermal conduction and mechanical properties.

[0006] Therefore, there is an urgent need to develop a novel diamond-copper composite heat dissipation substrate and its preparation technology that can be synergistically optimized at both the microscopic interface structure and macroscopic component distribution levels. Summary of the Invention

[0007] In view of this, the present invention provides a diamond-copper composite heat dissipation substrate and its preparation method, the purpose of which is to solve the technical problems of high interfacial thermal resistance, difficulty in matching thermal expansion coefficients, and weak interlayer bonding of gradient structure in the prior art of diamond-copper composite materials.

[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a diamond-copper composite heat dissipation substrate, comprising the following steps: (1) A titanium layer is deposited on the surface of diamond particles to obtain titanium-plated diamond particles; (2) After loading the titanium-plated diamond particles with catalyst metal salt, the catalyst metal salt is reduced in a hydrogen atmosphere to convert the catalyst metal salt into metal catalyst particles; then the atmosphere is switched to a carbon-containing gas atmosphere for heat treatment, so that the titanium layer grows outward from the catalyst particles as the center and is converted into a titanium carbide nanowire array in situ to obtain surface-modified diamond particles. (3) The surface-modified diamond particles are mixed with copper powder to obtain composite powder. The volume fraction of diamond particles is gradient-changed in the laying direction by layering and filling to form a powder blank. (4) Sinter the powder blank to obtain a densified composite block; (5) The composite block is annealed in a reducing atmosphere to obtain the diamond-copper composite heat dissipation substrate.

[0009] Furthermore, in step (1), a titanium layer is deposited by magnetron sputtering, and the thickness of the titanium layer is 50~300nm.

[0010] Furthermore, the catalyst metal salt mentioned in step (2) is nickel nitrate or iron nitrate, which is loaded onto the surface of titanium-plated diamond particles by impregnation.

[0011] Furthermore, the reduction treatment in step (2) is carried out at a temperature of 300~450℃ for 0.5~2h; the heat treatment is carried out at a temperature of 700~900℃ for 0.5~2h; and the carbon-containing gas is acetylene and / or methane.

[0012] Furthermore, the titanium carbide nanowires prepared in step (2) have a diameter of 30~150nm and a length of 1~10μm; the growth direction of the titanium carbide nanowire array is approximately perpendicular or inclined to the surface of the diamond particles.

[0013] Furthermore, in step (3), before mixing the surface-modified diamond particles with copper powder, a copper plating layer is coated on the surface of the surface-modified diamond particles by electrochemical deposition to form copper-coated composite particles, and then the copper-coated composite particles are mixed with copper powder for subsequent steps.

[0014] Furthermore, the layered laying in step (3) specifically involves: along the laying direction, the volume fraction of diamond particles gradually increases from 15-30% to 40-65%, while the average particle size of the diamond particles used decreases along this direction.

[0015] Furthermore, the sintering in step (4) is spark plasma sintering, with a temperature of 750~950℃, an applied pressure of 30~60MPa, and a time of 5~20min.

[0016] Furthermore, the reducing atmosphere mentioned in step (5) is a mixture of hydrogen and argon, the annealing temperature is 400~600℃, and the annealing time is 1~3 hours.

[0017] The present invention also provides a diamond-copper composite heat dissipation substrate prepared by the above preparation method.

[0018] Compared with the prior art, the technical solution of the present invention has the following significant advantages: 1. This invention grows a titanium carbide nanowire array in situ on the surface of diamond particles, rather than simply forming a dense carbide film. The titanium carbide nanowires extend outward from the diamond surface and are coated by a copper matrix, significantly increasing the interfacial contact area between diamond and copper. This creates a multi-level gradient interfacial structure, from diamond to a transition layer of titanium carbide, then to the titanium carbide nanowires, and finally embedded in the copper matrix. This structure constructs an efficient phonon transport channel between the diamond particles and the copper matrix, significantly reducing interfacial thermal resistance and greatly improving the overall thermal conductivity of the composite material.

[0019] 2. After titanium carbide nanowires are embedded in the copper matrix, a mechanical locking effect similar to "fiber anchoring" is formed at the interface. At the same time, the titanium carbide transition layer ensures chemical bonding. The synergistic effect of the two significantly enhances the interfacial bonding strength between diamond particles and the copper matrix, effectively suppressing interfacial debonding failure caused by the difference in thermal expansion coefficients during thermal cycling, and improving the service reliability of the heat dissipation substrate.

[0020] 3. Diamond particles are distributed in a gradient along the thickness direction within the copper matrix, giving one side of the heat dissipation substrate (high diamond volume fraction side) a low coefficient of thermal expansion matching the semiconductor chip, and the other side (low diamond volume fraction side) a higher coefficient of thermal expansion matching the package shell or solder layer, while maintaining good machinability and solderability. This gradient design enables a smooth transition of thermal stress within the heat dissipation substrate, reducing thermal mismatch stress concentration.

[0021] 4. This invention achieves controllable and uniform growth of titanium carbide nanowire arrays on the surface of diamond particles through a process route of "titanium layer deposition—catalyst precursor loading—hydrogen reduction—in-situ growth". Compared with the method of adding nanowires, the in-situ grown nanowires have a natural bonding strength with diamond particles, good dispersion uniformity, and avoid the problems of agglomeration and weak interfacial bonding that are difficult to overcome in the process of adding nanowires. Detailed Implementation

[0022] This invention provides a method for preparing a diamond-copper composite heat dissipation substrate, comprising the following steps: (1) A titanium layer is deposited on the surface of diamond particles to obtain titanium-plated diamond particles; In this invention, the titanium layer is deposited using magnetron sputtering, and the thickness of the titanium layer is 50-300 nm, preferably 100-250 nm, and more preferably 120-200 nm. The diamond particles are single-crystal diamond particles or polycrystalline diamond particles, with a particle size of 50-200 μm, preferably 70-150 μm. Before depositing the titanium layer, the diamond particles can be surface-cleaned and roughened to enhance the adhesion of the coating. The surface cleaning includes sequential ultrasonic cleaning with dilute nitric acid, acetone, and deionized water. The roughening treatment can be performed using molten alkali treatment or strong oxidizing acid treatment to create nanoscale etching pits on the diamond surface.

[0023] (2) After loading the titanium-plated diamond particles with catalyst metal salt, the catalyst metal salt is reduced in a hydrogen atmosphere to convert the catalyst metal salt into metal catalyst particles; then the atmosphere is switched to a carbon-containing gas atmosphere for heat treatment, so that the titanium layer grows outward from the catalyst particles as the center and is converted into a titanium carbide nanowire array in situ to obtain surface-modified diamond particles. In this invention, the catalyst metal salt is nickel nitrate or ferric nitrate. The titanium-plated diamond particles are immersed in an ethanol solution of nickel nitrate or ferric nitrate with a concentration of 0.05-0.5 mol / L, preferably 0.1-0.3 mol / L, and then dried to achieve loading. The reduction treatment is carried out under a hydrogen atmosphere at 300-450°C for 0.5-2 hours, causing the nickel nitrate or ferric nitrate to decompose and reduce into nano-nickel or nano-iron particles, which are then anchored on the titanium layer surface. The heat treatment temperature is 700-900°C, preferably 750-850°C, and the heat treatment time is 0.5-2 hours, preferably 1-1.5 hours. The carbon-containing gas is acetylene and / or methane, and the volume ratio of the carbon-containing gas to the carrier gas is 1:2-10. The obtained titanium carbide nanowires have a diameter of 30-150 nm, preferably 50-120 nm; a length of 1-10 μm, preferably 2-8 μm; and an aspect ratio of 20-200, preferably 30-150. The growth direction of the titanium carbide nanowire array is approximately perpendicular to or inclined to the surface of the diamond particles, which is beneficial to increasing the contact area with the copper substrate.

[0024] (3) The surface-modified diamond particles are mixed with copper powder to obtain composite powder. The volume fraction of diamond particles is gradient-changed in the laying direction by layering and filling to form a powder blank. In this invention, the copper powder is pure copper powder or copper alloy powder, with a particle size of 5-50 μm, preferably 10-40 μm, and a purity ≥99.9%. Preferably, before mixing the surface-modified diamond particles with the copper powder, a copper plating layer is coated onto the surface of the surface-modified diamond particles by electrochemical deposition to form copper-coated composite particles. The thickness of the copper plating layer is 1-10 μm, preferably 2-5 μm, and then the copper-coated composite particles are subsequently mixed with the copper powder. This copper plating layer can further improve the interfacial contact quality between the diamond particles and the copper substrate.

[0025] In this invention, the layered deposition method is as follows: along the deposition direction, the volume fraction of diamond particles gradually increases or decreases from one side to the other. Preferably, the volume fraction of diamond particles on the lower side is 15-30%, and the volume fraction on the higher side is 40-65%. More preferably, the volume fraction of diamond particles gradually transitions from 15-25% to 45-60%. The number of deposition layers is 3-10, preferably 4-8. More preferably, the average particle size of the diamond particles decreases along the direction of increasing volume fraction, that is, smaller diameter diamond particles are used on the high volume fraction side, and larger diameter diamond particles are used on the low volume fraction side, to further optimize thermal conductivity.

[0026] In this invention, preferably, the composite powder also contains nano-tungsten particles with a particle size of 20-100 nm, preferably 30-80 nm, and an addition amount of 0.5-3 wt%, preferably 1-2 wt%, of the total mass of the copper matrix. The nano-tungsten particles can anchor themselves at the copper grain boundaries during subsequent sintering, refining the grains and improving the matrix strength, while having minimal impact on thermal conductivity. The mixing can be carried out using a V-type mixer, a three-dimensional mixer, or a ball mill, with a mixing time of 2-6 hours, preferably 3-5 hours, to ensure uniform distribution of the components.

[0027] (4) Sinter the powder blank to obtain a densified composite block; In this invention, the sintering is spark plasma sintering, with a sintering temperature of 750-950℃, preferably 800-900℃, and more preferably 820-880℃; an applied pressure of 30-60 MPa, preferably 35-55 MPa, and more preferably 40-50 MPa; and a sintering time of 5-20 min, preferably 8-15 min. Spark plasma sintering can achieve densification at a lower temperature and in a shorter time, effectively suppressing the graphitization transformation of diamond particles and the excessive growth of copper grains. The sintering process is carried out in a vacuum atmosphere or an inert gas protective atmosphere.

[0028] (5) The composite block is annealed in a reducing atmosphere to obtain the diamond-copper composite heat dissipation substrate.

[0029] In this invention, the reducing atmosphere is a mixture of hydrogen and argon, with a hydrogen component of 5-20%, preferably 8-15%; the annealing temperature is 400-600℃, preferably 450-550℃; and the annealing time is 1-3 hours, preferably 1.5-2.5 hours. Annealing effectively eliminates residual thermal stress generated during sintering and reduces trace amounts of copper oxide that may form during sintering, further improving the thermal conductivity and mechanical property stability of the composite material.

[0030] The present invention also provides a diamond-copper composite heat dissipation substrate prepared by the above preparation method, comprising a copper substrate and diamond particles distributed inside the copper substrate. The surface of the diamond particles is at least partially covered by a titanium carbide transition layer. Titanium carbide nanowires are grown in situ on the titanium carbide transition layer. The titanium carbide nanowires extend outward from the surface of the diamond particles and are covered by the copper substrate. The diamond particles are distributed in a gradient along the thickness direction of the substrate within the copper substrate.

[0031] In this invention, the thickness of the titanium carbide transition layer is 20-200 nm, preferably 50-150 nm. The diameter of the titanium carbide nanowires is 30-150 nm, and the length is 1-10 μm. At least some of the titanium carbide nanowires on adjacent diamond particles intersect and overlap within the copper substrate, forming a three-dimensional titanium carbide nanowire thermally conductive network that penetrates the copper substrate, creating a highly efficient phonon transport channel. At the junction of the titanium carbide nanowire array and the titanium carbide transition layer, nano-nickel or nano-iron particles for catalytic growth are discretely distributed, and these nanoparticles are partially embedded in the titanium carbide transition layer and the roots of the titanium carbide nanowires.

[0032] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] Example 1 A method for preparing a diamond-copper composite heat dissipation substrate includes the following steps: (1) Select single-crystal diamond particles with a particle size of 100 μm, and ultrasonically clean them for 15 min each with dilute nitric acid, acetone and deionized water to remove surface oil and impurities. Then dry them in a vacuum drying oven at 80 °C for later use. Deposit a titanium layer on the surface of the diamond particles by magnetron sputtering. The sputtering target is a high-purity titanium target (purity ≥99.99%), the sputtering power is 150 W, the sputtering pressure is 0.5 Pa, the sputtering time is 30 min, and the titanium layer thickness is 150 nm to obtain titanium-plated diamond particles.

[0034] (2) Nickel nitrate hexahydrate (Ni(NO3)2·6H2O) was dissolved in anhydrous ethanol to prepare a nickel nitrate ethanol solution with a concentration of 0.2 mol / L. Titanium-plated diamond particles were immersed in the above solution, stirred for 30 min, filtered, and dried in a vacuum drying oven at 60 °C for 2 h to load nickel nitrate onto the surface of the titanium-plated diamond particles. The dried particles were placed in a tube furnace and reduced at 380 °C for 1 h under a hydrogen atmosphere (hydrogen flow rate 100 mL / min) to decompose and reduce nickel nitrate into nano-nickel particles and anchor them on the surface of the titanium layer. Subsequently, the gas was switched to a mixed atmosphere of acetylene and argon (acetylene flow rate 30 mL / min, argon flow rate 200 mL / min), the furnace temperature was raised to 800 °C, and held for 1.5 h to allow the titanium layer to grow outward from the nano-nickel particles as the catalyst center into a titanium carbide nanowire array. The furnace was then cooled to room temperature to obtain surface-modified diamond particles. The obtained titanium carbide nanowires have a diameter of 60~120nm and a length of 3~8μm.

[0035] (3) Take pure copper powder (particle size 30μm, purity ≥99.9%) and surface-modified diamond particles, and prepare two composite powders with diamond volume fractions of 20% and 55% respectively. Mix them in a V-type mixer for 4 hours to obtain uniform powder A (20% diamond) and powder B (55% diamond). In a graphite mold, layer by layer, first fill powder B, then gradually fill powder A, for a total of 5 layers. The diamond volume fraction of each layer along the filling direction is 55%, 45%, 35%, 25%, and 20% respectively, and the thickness of each layer is approximately the same to form a powder blank. The side with a diamond volume fraction of 55% corresponds to the chip mounting surface of the heat dissipation substrate.

[0036] (4) Place the graphite mold containing the powder blank into the spark plasma sintering furnace, apply an axial pressure of 40 MPa, heat it to 850°C at a heating rate of 100°C / min under vacuum conditions (vacuum degree ≤ 10 Pa), hold it at 10 min, and cool it to room temperature with the furnace to obtain a densified composite block.

[0037] (5) The composite block is placed in a tube furnace and annealed at 500°C for 2 hours in a mixed atmosphere of hydrogen and argon (hydrogen gas fraction of 10% and argon gas fraction of 90%) to eliminate sintering internal stress and reduce any possible copper oxide, thus obtaining a diamond-copper composite heat dissipation substrate.

[0038] Example 2 The difference between this embodiment and Embodiment 1 is that, in step (3), before mixing the surface-modified diamond particles with copper powder, an electrochemical deposition coating of copper is performed first, specifically: The surface-modified diamond particles obtained in step (2) were placed in an electrochemical deposition tank, using a copper sulfate plating solution system (CuSO4·5H2O 200g / L, H2SO4 50g / L) and a current density of 2A / dm³. 2 The temperature was 25°C, and the deposition time was 30 minutes. A copper plating layer with a thickness of 2-5 μm was coated onto the surface of the surface-modified diamond particles to form copper-coated composite particles. These copper-coated composite particles were then directly used as integral particles containing diamond and copper to prepare composite powders with diamond volume fractions of 20% and 55%, respectively. All other steps and parameters were the same as in Example 1.

[0039] Example 3 The difference between this embodiment and Embodiment 1 lies in the following steps and parameters: In step (1), the diamond particle size is 50 μm and the titanium layer thickness is 50 nm; In step (2), the concentration of nickel nitrate ethanol solution is 0.05 mol / L, the heat treatment temperature is 700℃, the heat treatment time is 2h, the acetylene flow rate is 20mL / min, and the argon flow rate is 200mL / min; the obtained titanium carbide nanowires have a diameter of 30~80nm and a length of 1~4μm. In step (3), the volume fraction of diamond in powder A is 15%, and the volume fraction of diamond in powder B is 40%. The volume fraction of diamond in each layer of the layered filling is 40%, 30%, 20%, and 15% along the filling direction. In step (3), nano tungsten powder (average particle size 50nm) is also added to the composite powder. The amount added is 1.5wt% based on the total mass of the copper matrix. That is, when preparing powder A and powder B, nano tungsten powder, surface-modified diamond particles, and copper powder are added together to the V-type mixer for mixing. In step (4), the sintering temperature is 750℃, the applied pressure is 30MPa, and the sintering time is 20min; In step (5), the annealing temperature is 400℃ and the annealing time is 3h.

[0040] The remaining steps and parameters are the same as in Example 1.

[0041] Example 4 The difference between this embodiment and Embodiment 1 lies in the following steps and parameters: In step (1), the diamond particles have a diameter of 150 μm and the titanium layer has a thickness of 300 nm. In step (2), the catalyst metal salt is ferric nitrate nonahydrate (Fe(NO3)3·9H2O) instead of nickel nitrate hexahydrate. A 0.5 mol / L ferric nitrate ethanol solution is prepared. The reduction treatment temperature is 450℃ and the reduction treatment time is 2 h. The heat treatment temperature is 900℃ and the heat treatment time is 45 min. The carbon-containing gas is methane instead of acetylene. The methane flow rate is 40 mL / min and the argon flow rate is 200 mL / min. The obtained titanium carbide nanowires have a diameter of 80~150 nm and a length of 5~10 μm. In step (3), the volume fraction of diamond in powder A is 30%, and the volume fraction of diamond in powder B is 65%. The volume fraction of diamond in each layer of the layered filling is 65%, 55%, 45%, 35%, and 30% respectively along the filling direction. The diamond particle size used in powder B is 70 μm, and the diamond particle size used in powder A is 120 μm. That is, the average particle size of the diamond particles increases from the high volume fraction side to the low volume fraction side. In step (4), the sintering temperature is 950℃, the applied pressure is 60MPa, and the sintering time is 5min; In step (5), the annealing temperature is 600℃, the annealing time is 1h, and the hydrogen gas integral is 20%.

[0042] The remaining steps and parameters are the same as in Example 1.

[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that the catalyst metal salt loading, hydrogen reduction treatment and carbon-containing gas heat treatment process in step (2) are omitted. That is, after step (1) is completed, the titanium-plated diamond particles are directly used for mixing and subsequent sintering in step (3).

[0044] In this comparative example, the diamond particles only have a titanium layer deposited by magnetron sputtering (a titanium carbide transition layer is formed by the reaction of titanium and diamond during sintering), and do not have a titanium carbide nanowire array structure.

[0045] The remaining steps and parameters are the same as in Example 1.

[0046] Comparative Example 2 The difference between this comparative example and Example 1 is that in step (3), the gradient distribution method of layered filling is not used. Instead, the surface-modified diamond particles obtained in step (2) are mixed with copper powder in a single ratio, with a diamond volume fraction of 40%, and uniformly filled into the mold in one go.

[0047] The remaining steps and parameters are the same as in Example 1.

[0048] Comparative Example 3 The difference between this comparative example and Example 1 is that the in-situ growth method of step (2) is not used, but instead, the method of "adding titanium carbide nanowires" is used. Specifically, after step (1) is completed, step (2) is not performed, but titanium carbide nanowires are prepared separately (using the carbothermal reduction method, with titanium dioxide and carbon nanotubes as raw materials, reacted at 1400℃ for 2h in an argon atmosphere). Then, the titanium-plated diamond particles, copper powder and added titanium carbide nanowires (3% of the mass of diamond particles) obtained in step (1) are mixed. Since the added nanowires are prone to agglomeration, high-energy ball milling is required for dispersion. The ball milling medium is cemented carbide balls, the ball-to-material ratio is 10:1, the ball milling speed is 300r / min, and the ball milling time is 3h. After ball milling, gradient laying and sintering are performed.

[0049] The remaining steps and parameters are the same as in Example 1.

[0050] Comparative Example 4 The difference between this comparative example and Example 1 is that in step (2), the titanium-plated diamond particles are directly heat-treated in a carbon-containing gas atmosphere, without prior catalyst metal salt loading and hydrogen reduction treatment steps. The specific operation is as follows: After step (1) is completed, the titanium-plated diamond particles are placed directly in a tube furnace and a mixed atmosphere of acetylene and argon is introduced (acetylene flow rate 30 mL / min, argon flow rate 200 mL / min), the temperature is raised to 800℃, and the temperature is maintained for 1.5 h.

[0051] The remaining steps and parameters are the same as in Example 1.

[0052] Performance testing The composite heat dissipation substrates prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to the following performance tests: 1. Thermal conductivity testing: The thermal diffusivity of the composite material was measured at room temperature using the laser flare method (LFA467, Netzsch). The thermal conductivity was calculated by combining the actual density and theoretical specific heat capacity measured by the Archimedes displacement method. The test sample was cut through along the thickness direction to obtain a complete sample containing all gradient layers. The overall thermal diffusivity throughout the thickness direction was measured, and the calculated thermal conductivity was the equivalent overall thermal conductivity of the gradient substrate.

[0053] 2. Coefficient of thermal expansion test: The linear coefficient of thermal expansion (CTE) of the substrate on the high diamond volume fraction side and the low diamond volume fraction side was measured using a thermomechanical analyzer (TMA402F3, Netzsch) in the temperature range of 25~200℃. The heating rate was 5℃ / min. The CTE test sample on the high volume fraction side was cut from the surface of the substrate on the high diamond volume fraction side, and the CTE test sample on the low volume fraction side was cut from the surface of the substrate on the low diamond volume fraction side.

[0054] 3. Interfacial Thermal Conductivity Assessment: Based on the effective medium theory and obtained actual thermal conductivity data, combined with the microstructure parameters of the composite material (diamond volume fraction, diamond particle size, titanium carbide nanowire size and distribution density), the thermal conductivity of the diamond-copper interface is back-calculated and assessed. Higher interfacial thermal conductivity indicates lower interfacial thermal resistance.

[0055] 4. Thermal Cycling Reliability Test: The samples were subjected to thermal cycling within a temperature range of -55℃ to +150℃, with each cycle lasting 30 minutes (heating rate approximately 20℃ / min, cooling rate approximately 20℃ / min, and holding at both high and low temperatures for 5 minutes), for a total of 500 cycles. The thermal conductivity of the samples before and after thermal cycling was measured, and the rate of decrease in thermal conductivity was calculated to evaluate the thermal stability of the interfacial bonding.

[0056] Table 1 Test results of the examples and comparative examples

[0057] *Note: Comparative Example 2 shows a uniformly distributed structure, without distinguishing between the high-volume-fraction side and the low-volume-fraction side; its overall CTE is 10.5 × 10⁻⁶. -6 / K.

[0058] The test results above show that: The composite heat dissipation substrates prepared in Examples 1-4 all exhibited excellent thermal conductivity (652-712 W / (m·K)) and good gradient thermal expansion characteristics. The high diamond volume fraction side had a low coefficient of thermal expansion (5.2-6.3 × 10⁻⁶). -6 / K), which can be well matched with semiconductor chips; the low diamond volume fraction side has a high coefficient of thermal expansion (12.6~14.8×10). -6 / K), which facilitates connection with the packaging shell and alleviates thermal stress. Meanwhile, the interfacial thermal conductivity is as high as 78~105MW / (m²). 2 After 500 thermal cycles, the thermal conductivity decreased by only 1.6-2.8%, indicating excellent interfacial bonding strength and thermal stability.

[0059] Example 2: By pre-coating the surface-modified diamond particles with a copper layer, the contact state between the diamond particles and the copper substrate was further improved, effectively filling the gaps between the nanowires. The thermal conductivity and interfacial thermal conductivity both reached their maximum values ​​of 712 W / (m·K) and 105 W / (m·K), respectively. 2 ·K).

[0060] In Example 3, nano-tungsten particles were added and a smaller diamond particle size was used. The nano-tungsten particles played a role in grain refinement and dispersion strengthening in the copper matrix. The performance degradation rate after thermal cycling was 2.8%, which is still at a low level, and it has good overall performance.

[0061] Comparative Example 1, lacking a titanium carbide nanowire array structure, relies solely on a dense titanium carbide transition layer for heat transfer, resulting in a limited interfacial contact area and an interfacial thermal conductivity of only 35 MW / (m²). 2 The thermal conductivity was only 478 W / (m·K), which was about 30% lower than that of Example 1, and the performance degraded significantly after thermal cycling, with a thermal conductivity decrease rate of 5.8%.

[0062] Comparative Example 2 lacks a gradient distribution structure. Although it has a high thermal conductivity (670 W / (m·K)), it cannot simultaneously meet the thermal expansion matching requirements on both sides, and its overall CTE is 10.5 × 10⁻⁶. -6 / K cannot simultaneously meet the requirements of low CTE on the chip side and high CTE on the package side.

[0063] Comparative Example 3 used titanium carbide nanowires. Due to poor dispersion uniformity of the nanowires and lack of chemical bonding with the diamond particles, the nanowires were unevenly distributed in the copper matrix, exhibiting significant agglomeration. The thermal conductivity was only 531 W / (m·K), and the interfacial thermal conductivity was only 42 MW / (m·K). 2The K values ​​are all far lower than the in-situ growth scheme of this invention, and the thermal cycling stability is also significantly insufficient, with a decrease rate of 4.9%.

[0064] In Comparative Example 4, without the introduction of a catalyst, after heat treatment in a carbon-containing gas atmosphere, only a dense titanium carbide layer could be formed, and the nanowire array structure could not be grown. Its thermal conductivity was 505 W / (m·K), and the interfacial thermal conductivity was only 38 W / (m·K). 2 The concentration of K (K) is essentially the same as in Comparative Example 1, further verifying the crucial role of the catalyst in the in-situ growth of titanium carbide nanowire arrays. The catalyst particles provide preferential nucleation sites for the growth of titanium carbide nanowires, which is a necessary condition for realizing the core mechanism of "growth outward from the catalyst particle center".

[0065] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a diamond-copper composite heat dissipation substrate, characterized in that, Includes the following steps: (1) A titanium layer is deposited on the surface of diamond particles to obtain titanium-plated diamond particles; (2) After loading the titanium-plated diamond particles with catalyst metal salt, the catalyst metal salt is reduced in a hydrogen atmosphere to convert the catalyst metal salt into metal catalyst particles; then the atmosphere is switched to a carbon-containing gas atmosphere for heat treatment, so that the titanium layer grows outward from the catalyst particles as the center and is converted into a titanium carbide nanowire array in situ to obtain surface-modified diamond particles. (3) The surface-modified diamond particles are mixed with copper powder to obtain composite powder. The volume fraction of diamond particles is gradient-changed in the laying direction by layering and filling to form a powder blank. (4) The powder blank is sintered to obtain a densified composite block; (5) The composite block is annealed in a reducing atmosphere to obtain the diamond-copper composite heat dissipation substrate.

2. The preparation method according to claim 1, characterized in that, In step (1), a titanium layer is deposited by magnetron sputtering, and the thickness of the titanium layer is 50~300nm.

3. The preparation method according to claim 2, characterized in that, The catalyst metal salt mentioned in step (2) is nickel nitrate or iron nitrate, which is loaded onto the surface of titanium-plated diamond particles by impregnation.

4. The preparation method according to claim 3, characterized in that, The reduction treatment in step (2) is performed at a temperature of 300~450℃ for 0.5~2h; the heat treatment is performed at a temperature of 700~900℃ for 0.5~2h; and the carbon-containing gas is acetylene and / or methane.

5. The preparation method according to any one of claims 1 to 4, characterized in that, The titanium carbide nanowires prepared in step (2) have a diameter of 30~150nm and a length of 1~10μm; the growth direction of the titanium carbide nanowire array is approximately perpendicular or inclined to the surface of the diamond particles.

6. The preparation method according to claim 5, characterized in that, In step (3), before mixing the surface-modified diamond particles with copper powder, a copper plating layer is coated on the surface of the surface-modified diamond particles by electrochemical deposition to form copper-coated composite particles, and then the copper-coated composite particles are mixed with copper powder for subsequent steps.

7. The preparation method according to claim 1 or 6, characterized in that, The layered laying in step (3) specifically involves increasing the volume fraction of diamond particles from 15-30% to 40-65% along the laying direction, while the average particle size of the diamond particles used decreases along this direction.

8. The preparation method according to claim 7, characterized in that, The sintering described in step (4) is spark plasma sintering. The temperature of spark plasma sintering is 750~950℃, the pressure applied is 30~60MPa, and the time is 5~20min.

9. The preparation method according to claim 8, characterized in that, The reducing atmosphere mentioned in step (5) is a mixture of hydrogen and argon, the annealing temperature is 400~600℃, and the annealing time is 1~3 hours.

10. The diamond-copper composite heat dissipation substrate prepared by the preparation method according to any one of claims 1 to 9.